RESOLUSI KONFLIK DI ASIA TENGGARA PERSPEKTIF ISLAM (STUDI KASUS RESOLUSI KONFLIK CHAM ISLAM DALAM MENGHADAPI SINKRETISME ISLAM DI VIETNAM) - Febi Eka Putri; Eva Fadhilah (Al Qisthas Jurnal Hukum dan Politik, 2022)
Vietnam is one of the countries in Southeast Asia in the form of a Socialist country. The majority of the population in Vietnam embraces Buddhism while Islam is a minority religion there. The Muslim population in Vietnam is divided into two sects or schools, namely Cham Islam and Cham Bani. Cham Islam is a follower of the Sunni sect of Islam while Cham Bani is a sect of Islam that is still influenced by Indian culture or traditions. This study examines the resolution of the Cham Islam conflict in the face of Islamic syncretism in Vietnam from an Islamic perspective. With qualitative research methods, the authors found that the conflict resolution used in reducing conflicts that occurred because of differences in flow between Cham Islam and Cham Bani was a persuasive approach using the method of deliberation as taught by Islam. Another method when the method of deliberation is not achieved is the method of war. War in conflict resolution is not meant to solely kill lives but to survive and defend religion when threatened.   Keywords: Resolution, Conflict, Vietnam, Islam